Functional Finance: What, Why, and How? - Stephanie Bell (Levy Economics Institute of Bard College, 1999)
The purpose of this paper is threefold. First, the theory of functional finance, as explicated by its originator, Abba P. Lerner, is put forward. Second, the reader is introduced to the use, standard in money and banking texts, of T-account balance sheet entries. Although no important conclusions will rest solely on the reader's ability to cope with these entries, comfort with their use will ease the exposition. An appendix therefore is provided to assist those not yet exposed to this method of recording balance sheet changes and for those who merely wish to refresh themselves. The third purpose of the paper is to demonstrate the need for policies governed by the principles of functional finance.
Keywords: 330